The spirit of Malaysia incorporated and privatisation / Sharifah Zannierah Syed Marzuki …[et al.] - Syed Marzuki, Sharifah Zannierah; Yahya, Wan Kalthom; Mahmod, Razmah; Hashim, Hasnizawati; A.Halid, Rozieana (2005)
Malaysia is ready to become a developed country in the year 2020. In achieving it, we must welcome all the obstacles and challenges in order for us to become a great nation. One of the most challenging tasks of a government is introducing radical changes to national policy. New and right attitudes must be instilled towards a particular national goal. Malaysia Incorporated and Privatisation are two concepts in modernizing the Malaysian economy.